High-tech internet start-ups in India - Krishna, H. S., 1978- (Cambridge : Cambridge University Press, 2019)
Technology entrepreneurship has been receiving growing importance as an effective instrument to promote national economic growth, both from empirical researchers and policymakers. India has emerged as the third largest base for high-tech start-ups in the world. Although there is a surge in start-up creation rates in India, little is known about factors required for these start-ups to survive, sustain and grow into large enterprises, particularly in the context of emerging economies like India. This book reviews the entrepreneurial, firm-specific and external environment-specific aspects that influence the key lifecycle stages of high-tech start-ups and identifies the key factors that influence each milestone. Existing literature in this subject has limited studies on the structure of the high-tech start-up sector and processes and strategies adapted by them. This book aims to address this gap, analyzing case studies and empirical data, and provides a multidimensional framework to understand the life cycle of high-tech start-ups.
Title from publisher's bibliographic system (viewed on 19 Jun 2019).
Keywords: High technology industries -- India; New business enterprises -- India; Electronic commerce -- India; Internet industry -- India